Entropy’s Critical Translations: Following Serres’s Path through the North-West-Passage - Kroth, Lilian (Technophany, A Journal for Philosophy and Technology, 2025)
It is, according to Serres, the ‘greatest discovery of history that entropy and information are connected’ – a line of thought he takes throughout epistemological questions, aesthetics, cultural analysis, and a theory of matter. By following Serres’s work, one finds negentropy, entropy, chaos, local orders, the ‘soft’, and the ‘hard’ almost everywhere in his writings. The intellectual context and sources that Serres draws on are an important support to understand the way in which the coupling of informational and thermodynamic entropy takes place, and how it becomes a key operator of entropic differentiation. This text draws a combinatorial map of how Serres connects understandings of entropy across a range of areas of knowledge. In this specific context, Serres’s path of translation harnesses the so-called ‘hard’ and the ‘soft’ forms of entropy in looking at literature and arts, yet also to discuss social phenomena and the formations of societies. By drawing attention to the negative spaces in Serres’s connective path of translating entropies, and in the course of reading his work in context with other philosophies of entropy, this section aims to explore Serres’s translations in the way it both connects and leaves gaps. Approaching Serres’s criticality in this way brings one to the critical, difficult, icy landscapes of the North-West-Passage and the role it plays in his work. The North-West-Passage epitomises a ‘method’ to conceive the difficult path between the natural sciences and the humanities – exactly the kind of path that ‘entropy’ often meanders on. In fact, entropy itself plays an important role in regard the icy landscape’s ecology, e.g. to the degree to which the passage is melted or frozen, and thus, to the possibility of the passage as such. By bringing these multi-layered aspects of entropy as a material, aesthetic, and critical factor together, this contribution places Serres’s take on entropy as an eco-critical path in the face of the melting of icy landscapes.